The rise of ransomware: a review of attacks, detection techniques, and future challenges - Kamil, Samar; Siti Norul Huda, Sheikh Abdullah; Ahmad Firdaus, Zainal Abidin; Usman, Opeyemi Lateef (Institute of Electrical and Electronics Engineers Inc., 2022)
Cybersecurity is important in the field of information technology. One most recent pressing issue is information security. When we think of cybersecurity, the first thing that comes to mind is cyber-attacks, which are on the rise, such as Ransomware. Various governments and businesses take a variety of measures to combat cybercrime. People are still concerned about ransomware, despite numerous cybersecurity precautions. In ransomware, the attacker encrypts the victim's files/data and demands payment to unlock the data. Cybersecurity is a collection of tools, regulations, security guards, security ideas, guidelines, risk management, activities, training, insurance, best practices, and technology used to secure the cyber environment, organization, and user assets. This paper analyses ransomware attacks, techniques for dealing with these attacks, and future challenges.